George Herbert Mead and the Theory of the Self - Leonavičius, Vylius (Sociologija. Mintis ir veiksmas, 1998)
Mead’s theory defines the individual as a rational and an active being. While at the time Freud’s influence was substantial, the notion of the unconscious plays a limited role in Mead's discussion of the rational ‘me’ or the ego. Most often the unconscious refers to social action that is not thought of consciously. The main object of Mead's analysis is the self and its bases in the social interaction.
Keywords: George Herbert Mead; Sigmund Freud; self; unconcious; Herbert Cooley; William James; John Dewey